ANALISIS PENDAPATAN USAHA TANI DAN TATANIAGA TANAMAN TOMAT (Solanum lycopecumL.) DI DESA SEMANGAT KECAMATAN MERDEKA KABUPATEN KARO - Frans Nico Sitanggang; Juliana Br Simbolon; Fandri Siburian (JURNAL REGIONOMIC, 2020)
Analysis of farm business and commerce of tomato plant (Solanum lycopecum L.) in Semangat village Merdeka subdictrict Karo regency. This aim of study is to analyse productivity, production cost dan farmer income to find out whether the cultivation of farm business and the proprierty of tomato farm culitvation in the research area. This study results show that production cost are huge by Rp 29.848.529 a hectare. The receipt was gained by Rp144.066.667 a hectare and tomato’s farmer income by Rp 19.036.356 a month. The farm business tomato plant worthy to be implemented and developed in view of worthiness criteria R/C ratio is R/C > 1 is by 5,08 a hectare. Based on analyse Break Event Point can it e know that BEP tomato farm cultivation a hectare so far beyond the point of impact, that is to say, an average of 1,523,128/kg an BEP cost a hectare by Rp4,451/kg. Meanwhile, the sector has two commerce channels in the reseach area : Farmer- harvester-Retail grocer-final stage commander (Channel I) and Farmer- harvester-great merchant-Retail grocer (Channel II). The function of commerce what is done is an exchange and purchase function, physic function (transportation, loading and packaging) and fasility function (marketing loss and retribution). Commerce margin on first commerce channel is Rp8.871/kg and commerce margin on first commerce channel is Rp 16.871/kg. The commerce channel in reaearch area with efesien value is 1,07 and 1,30 ( e > 1 ).